Legal narratives in Chinese, American, British, Japanese, and South Korean films and comparative research on civic legal education - Song, Mujie; Jin, Jiemei; Hou, Danni; Zheng, Shaoxin (Frontiers in Education, 2025)
IntroductionLegal films across nations exhibit significant differences in their modes of expression, which stem not only from the structural distinctions between the Civil Law System and Common Law System, but more deeply from the differing emphases in each country’s socio-legal ideology.MethodsTo explore the role and mechanisms of legal films in contemporary civic legal education, this study selects representative films from China, the United States, the United Kingdom, Japan, and South Korea. The research integrates Critical Legal Culture Theory with a comparative analytical approach, first constructing a multi-dimensional analytical framework based on theories of legal consciousness and narrative communication, and then applying this framework to compare the films’ narrative strategies, visual representations, and implied legal-cultural values.ResultsFindings reveal that legal films from the Common Law System tend to emphasize procedural justice and the struggle for litigation rights, highlighting institutional tensions. In contrast, films from the Civil Law System prioritize ethical concerns and the humanization of legal institutions, often presenting a more tempered critique and promoting systemic reconciliation. The educational efficacy of legal films lies in the complementarity between legal knowledge transmission and emotional engagement. This dual function enhances public understanding of legal principles while fostering a sense of institutional trust.DiscussionEstablishing intercultural interpretive frameworks and integrating legal films into structured civic education programs are essential steps toward advancing public legal consciousness and the development of civic legal education.